2010
DOI: 10.1891/0739-6686.28.191
|View full text |Cite
|
Sign up to set email alerts
|

The Health Care Work Environment and Adverse Health and Safety Consequences for Nurses

Abstract: Nurses' working conditions are inextricably linked to the quality of care that is provided to patients and patients' safety. These same working conditions are associated with health and safety outcomes for nurses and other health care providers. This chapter describes aspects of the nursing work environment that have been linked to hazards and adverse exposures for nurses, as well as the most common health and safety outcomes of nursing work. We include studies from 2000 to the present by nurse researchers, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 108 publications
1
51
0
Order By: Relevance
“…Programmes have been implemented and outcomes have been measured in several settings (Brogmus et al 2007;Gallagher and Scott 1997;Geiger-Brown and Lipscomb 2011;Grabiner et al 2008;Menant et al 2008). If obesity proves, in confirmatory studies, to be a prominent risk factor, prevention programmes could take this into account.…”
Section: Discussionmentioning
confidence: 99%
“…Programmes have been implemented and outcomes have been measured in several settings (Brogmus et al 2007;Gallagher and Scott 1997;Geiger-Brown and Lipscomb 2011;Grabiner et al 2008;Menant et al 2008). If obesity proves, in confirmatory studies, to be a prominent risk factor, prevention programmes could take this into account.…”
Section: Discussionmentioning
confidence: 99%
“…33 These findings are supported in a review that examined the relationship between PSC and nurses’ health and safety behaviours and outcomes. 34 Similarly, Gershon et al demonstrated that SP compliance was strongly correlated with organizational commitment to safety. 21 Advancing this knowledge, DeJoy et al found that a negative safety climate was the strongest predictor of job hindrances, which in turn were the strongest predicators of lower SP adherence.…”
Section: Introductionmentioning
confidence: 96%
“…[3][4][5][6][7] In Eastern country, perceived physical demands were associated with MSDs (OR = 2.04 to 7.24). 8 Studies in Western countries reported that highly demands at work increased MSDs (OR = 12.0).…”
Section: Introductionmentioning
confidence: 99%